Complex systems, part I: why 42 is rarely, if ever, the ultimate answer. Issue 2 (February 2020) - Mitchell, D.A.; Sebald, A.; Tomasello, L.
Abstract: We describe the different categories of systems and systems thinking, and illustrate why almost all clinical interactions constitute simultaneously complex and complicated systems, so-called "wicked systems". We also discuss why they are not amenable to quantitative analysis. With the use of comparisons and illustrations we show some of the problems that reductionist metrics create, and support concerns regarding quantitative fallacy. The systematic correlation of data in medicine was one of the earliest achievements of the discipline. Recently, however, the overwhelming bias towards an evidence base, which relies almost entirely on randomised controlled trials, has created a reductionist view that often excludes important aspects of medicine and, in particular, surgery. We must now move away from thinking that is controlled by the "tyranny of metrics" to embrace complex-systems thinking, and work across disciplines. We outline the arguments for this and give clinical examples from oral and maxillofacial surgery.